THE EFFECT OF WORK STRESS ON EMPLOYEE PERFORMANCE WITH EMOTIONAL INTELLIGENCE AS A MODERATING VARIABLE - Setyanto Putro; Nur Wening (International Journal of Innovative Technologies in Social Science, 2022)
This study aims to analyze the effect of work stress on employee performance with emotional intelligence as a moderating variable. This type of research is descriptive quantitative. The object of research is PT. X and the subject in this study is using the Slovin formula. The sample selection was 87 samples. All data have met the classical assumption test and the regression model has met the model feasibility test. Based on the discussion that has been done, it can be concluded that work stress and emotional intelligence have a positive and significant effect on employee performance, emotional intelligence increases the effect of work stress on employee performance. Job stress is a major problem both for employees and for organizations.